The history of money From bartering to banking. - Jenkins, Martin (2014)
With clarity and humor, Martin Jenkins and Satoshi Kitamura take readers on a fascinating tour of the history of money. What can take the form of a stone with a hole in the middle, a string of shells, a piece of paper, or a plastic card? The answer is money, of course. But when did we start using it? And why? What does money have to do with writing? And how do taxes and interest work? From the Stone Age to modern banking, this lighthearted and engaging account traces the history of the stuff that makes the world go round.
Text Difficulty 5
MG/Middle grades (4th-8th)
1160
6.3
Electronic reproduction.
Keywords: Juvenile Nonfiction; Reference; Sociology; Electronic books